PRIVATIZAÇÃO, POLUIÇÃO E LUCRO NA REGIÃO DO BAIXO SÃO FRANCISCO-SE: UMA ABORDAGEM SOB A PERSPECTIVA DA ÉTICA SOCIOAMBIENTAL - Santos Matos, Silvia Maria; Becker, Evaldo (Prometheus - Journal of Philosophy., 2020)
This article intends to examine from an interdisciplinary point of view, the ethical and technological issues involved in the use and access to water resources, in the region of Baixo São Francisco in Sergipe, specifically around its mouth, located in the municipality of Brejo Grande. In this article, the use of water mainly with regard to shrimp farming practiced predatory on the banks of the river, which suppresses all existing vegetation and kills native aquatic species through fertilizers and chemicals used in this process, harming riverside populations. The reflections presented here are elaborated in the light of ancient and current theories, which examined and continue to examine water as a common good of universal value and vital element indispensable to the life of all species.